Estimation of divergences on time scales via the Green function and Fink’s identity - Iqrar Ansari (Advances in Difference Equations, 2021)
Abstract The aim of the present paper is to obtain new generalizations of an inequality for n-convex functions involving Csiszár divergence on time scales using the Green function along with Fink’s identity. Some new results in h-discrete calculus and quantum calculus are also presented. Moreover, inequalities for some divergence measures are also deduced.